2019
DOI: 10.1371/journal.pone.0215153
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Alberta Context Tool in a multi-site Australian Emergency Department nurse population

Abstract: The organisational context of healthcare settings has an essential role in how research evidence is used in clinical practice. The Alberta Context Tool (ACT) measures 10 concepts of organisational context with higher scores indicating a more positive work environment and potentially better use of research evidence in patient care. We assessed the psychometric properties of the ACT in Emergency Departments (EDs). This validation study was conducted as part of a multi-centre trial of triage, treatment and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In line with previous validation studies of the ACT [21,23,38], we used three factor models: one for all items, one for items included in the seven scale-based concepts and one for items included in the three count-based concepts, as recommended by the copyright holders [23]. Similar to the previous validation studies, we found improvement in model fit when excluding the count-based items.…”
Section: Structural Validitymentioning
confidence: 57%
See 1 more Smart Citation
“…In line with previous validation studies of the ACT [21,23,38], we used three factor models: one for all items, one for items included in the seven scale-based concepts and one for items included in the three count-based concepts, as recommended by the copyright holders [23]. Similar to the previous validation studies, we found improvement in model fit when excluding the count-based items.…”
Section: Structural Validitymentioning
confidence: 57%
“…The ACT showed acceptable validity both in terms of reliability and structural validity, measured using confirmatory factor analyses. The English version of the ACT has previously been thoroughly validated by the tool developers and others, in different healthcare settings [19][20][21]38]. Translated versions of the ACT have also been validated in Swedish [22] and German studies [23].…”
Section: Plos Onementioning
confidence: 99%
“…Higher scores indicate a more positive perception of organizational context. The ACT has been validated extensively demonstrating good psychometric properties Estabrooks, Squires, Hayduk, Cummings, & Norton, 2011), including a comprehensive validation in our own population of emergency nurses that confirmed the factor structure of the ACT and showed Cronbach's alphas of excellent internal consistency (a > 0.7) for 9 of 10 ACT domains (Schadewaldt et al, 2019).…”
Section: Emergency Nurse Surveymentioning
confidence: 62%
“…Some studies focused on particular types of departments such as emergency departments (e.g. Schadewaldt et al, 2019) or intensive care units. Four studies were concerned with primary care (e.g.…”
Section: Resultsmentioning
confidence: 99%